2022
DOI: 10.1063/5.0090270
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser-induced sub-wavelength plasma inside dielectrics. II. Second-harmonic generation

Abstract: Second-harmonic emission at a frequency that is twice the laser frequency is an important diagnostic for nonlinear laser–plasma interaction. It is forbidden for centrosymmetric materials such as the bulk of sapphire. The symmetry, however, can be broken by dielectric discontinuities as a result of plasma generation inside a solid dielectric. In the present work, we explore the basic characteristics of experimentally observed second-harmonic emission during focusing a femtosecond Bessel beam inside sapphire. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…We anticipate that measurement of the second harmonic can provide further insights into the absorption mechanisms at play during the interaction of femtosecond pulses with solid dielectrics. In a forthcoming work, Ardaneh et al 49 , we will explicitly compare the second harmonic generation from the experiments with the PIC simulations. Further work will be dedicated to simulations of the ionization dynamics within PIC simulations to provide the plasma evolution during the interaction of femtosecond pulses with solid dielectrics.…”
Section: Discussionmentioning
confidence: 99%
“…We anticipate that measurement of the second harmonic can provide further insights into the absorption mechanisms at play during the interaction of femtosecond pulses with solid dielectrics. In a forthcoming work, Ardaneh et al 49 , we will explicitly compare the second harmonic generation from the experiments with the PIC simulations. Further work will be dedicated to simulations of the ionization dynamics within PIC simulations to provide the plasma evolution during the interaction of femtosecond pulses with solid dielectrics.…”
Section: Discussionmentioning
confidence: 99%
“…In the outward propagation of hot electrons, electrostatic ambipolar fields form at the plasma surface due to the different inertia of the electron and ion. Moreover, in the second article of this series (Ardaneh et al, 39 Paper II hereafter), we reported the second-harmonic generation by a second-order current of hot electrons near the critical surface. The electron currents form by the resonance absorption and radiation force of the incident laser wave.…”
Section: Introductionmentioning
confidence: 86%
“…In our simulation, we used the plasma parameters that could reproduce our experimental measurements (far-field, near-field, absorp-tion) as reported in Paper I, 38 and II. 39 The simulation setup is summarized in Table I. The plasma is fully ionized and composed of electrons and ions with equal densities (to preserve electric neutrality) given by n = n max exp(−x 2 /w 2 x ) exp(−y 2 /w 2 y ) tanh(z µm ) with FWHM x = √ 2 ln 2w x = 250 nm, and FWHM y = √ 2 ln 2w y = 600 nm.…”
Section: Pic Simulationmentioning
confidence: 99%
See 2 more Smart Citations